2020
DOI: 10.1177/1059840520970847
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Positive School Climate on Suicidality and Mental Health Among LGBTQ Adolescents: A Systematic Review

Abstract: Lesbian, gay, bisexual, transgender, and queer/questioning (LGBTQ) adolescents are more likely to report suicidality and worse mental health than their heterosexual peers. We conducted a systematic review to examine the relationship between positive school climate and suicidality and mental health among LGBTQ adolescents. We searched the literature using PubMed, PsycINFO, and CINAHL. Six studies met inclusion criteria, and all had low to moderate risks of bias. Results indicate that LGBTQ students in schools w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(42 citation statements)
references
References 52 publications
0
33
0
1
Order By: Relevance
“…A maioria dos estudantes pesquisados, independentemente da orientação sexual, demonstrou desconhecimento sobre os aspectos que envolvam a vida LGBT na universidade, quer no âmbito de políticas públicas, quer no apoio institucional a esta população. O que diverge do observado em outros estudos, nos quais os acadêmicos afirmam não haver inclusão em suas respectivas instituições [40,41,42].…”
Section: Discussionunclassified
“…A maioria dos estudantes pesquisados, independentemente da orientação sexual, demonstrou desconhecimento sobre os aspectos que envolvam a vida LGBT na universidade, quer no âmbito de políticas públicas, quer no apoio institucional a esta população. O que diverge do observado em outros estudos, nos quais os acadêmicos afirmam não haver inclusão em suas respectivas instituições [40,41,42].…”
Section: Discussionunclassified
“…Researchers have delved into the psychosocial experiences of lesbian, gay, bisexual, and transgender (LGBT) adults in the past few decades, while we still need to learn more about transgender experiences ( Ancheta et al, 2021 ; Marshall & Cahill, 2021 ). It has generally been observed that LGBT older adults have poorer mental health and more significant mental distress than heterosexual older adults ( Zay Hta et al., 2021 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Medical professionals assign "sex" at birth based on physical characteristics and sexual organs of the new-born. Even then, there is a small percentage of the population (about 1.7%, comparable to the amount of people born with red hair (Amnesty International, 2018 [8]) born as "intersex" babies; that is, infants who present with both male and female physiological, hormonal or genetic characteristics.…”
Section: Understanding Sex and Gendermentioning
confidence: 99%